2004
DOI: 10.1007/s00024-003-2488-8
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity and Seismic Hazard in Alexandria (Egypt) and its Surroundings

Abstract: Alexandria City has suffered great damage due to earthquakes from near and distant sources, both in historical and recent times. Sometimes the source of such damages is not well known. Seismogenic zones such as the Red Sea, Gulf of Aqaba-Dead Sea Hellenic Arc, Suez-Cairo-Alexandria, Eastern-Mediterranean-Cairo-Faiyoum and the Egyptian costal area are located in the vicinity of this city. The Egyptian coastal zone has the lowest seismicity, and therefore, its tectonic setting is not well known.The 1998 Egyptian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…These are referred to as the Baltim, Temsah and Rosetta trends, respectively (Abdel Aal et al, 1994). Also, the study area is located near to the Nile Delta cone which is considered as a large hinge zone that consists of several southward half-grabens (El-Sayed et al, 2004) as shown in Fig. 4.…”
Section: Geological and Tectonic Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are referred to as the Baltim, Temsah and Rosetta trends, respectively (Abdel Aal et al, 1994). Also, the study area is located near to the Nile Delta cone which is considered as a large hinge zone that consists of several southward half-grabens (El-Sayed et al, 2004) as shown in Fig. 4.…”
Section: Geological and Tectonic Settingsmentioning
confidence: 99%
“…About 14 of these earthquakes were located mainly in the Hellenic Arc region with relatively large magnitudes. The other nine earthquakes are located off-shore of Alexandria City with moderate magnitude (El-Sayed et al, 2004). In terms of seismic risk, the unconsolidated sediment materials could amplify ground motion during earthquakes and this causes building on these grounds to become more vulnerable to earthquake damage than those built above the hard rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Papadopoulos and Chalkis, 1984;Papazachos and Papazachou, 1998;Soloviev et al, 2000;Papadopoulos, 2003;El-Sayed et al, 2004;Tinti et al, 2004;Papadopoulos and Fokaefs, 2005;Stefatos et al, 2006;Papadopoulos et al, 2014). The Aegean Sea and its surrounding areas, in particular, are not only the most active Mediterranean regions in terms of seismicity and tectonic movements, but their coastlines have also experienced numerous tsunami events in recent, historic and pre-historic times.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Major historical tsunamis in the eastern Mediterranean region which affected northern Egypt are triggered by large earthquakes (Papadopoulos et al, 2014). However, there is a possibility of landslide triggered tsunamis associated with local earthquakes (El-Sayed et al, 2004;Tinti et al, 2005). Yalciner et al (2014) estimated from modelling that a landslide with a volume up to 500 km 3 may have caused a tsunami with a wave height ranging from 0.4 to 4 m offshore of the Nile Delta.…”
Section: Introductionmentioning
confidence: 99%